Pengembangan Model Pendidikan Karakter Religius dan Disiplin di SMP IT Nurul Islam Tengaran Tahun 2019 - Purwoko, Purwoko (CV. Creative Tugu Pena, 2020)
This article was to find out and develop the model of character education, specially discipline and religious characters. The background of this research was the implementation of religious character wasn’t maximal yet and the students discipline level was still low. So, the solution to resolve this problem is when the implementation of religious and discipline character is truly realized maximally. The subjects or the respondents of this research were teachers and the supervisors of dormitory at SMPIT Nurul Islam Tengaran. This article used R&D (Research and Developmen). The result of data analysis qualitatively showed that the needed of the level of religious and discipline characters was still under the good-enough level. So the development of this two kinds of characters is needed. And for the effectiveness level of development of religious educational character quantitatively showed that the result of t count = 12,223, with the value of df = 35 and significant value is 0,05 so the t table = 1,684, Ha is accepted because t count is on the Ha acceptance area. On the other side, the result of the discipline educational character showed that t count = -11,361, with the value of df=35 and the significant value is 0,05 so with the t table = 1,684, Ha is accepted because t count is also on the Ha acceptance area. The result of the development of the discipline and religious characters can be used effectively Keywords: Educational Character, Model of Educational Character Religious